2006
DOI: 10.1182/blood-2005-11-011486
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial uniparental isodisomy at clustered breakpoint intervals is a frequent mechanism of NF1 inactivation in myeloid malignancies

Abstract: To identify the mechanism of loss of heterozygosity (LOH) and potential modifier gene(s), we investigated the molecular basis of somatic NF1 inactivation in myeloid malignancies from 10 children with neurofibromatosis type 1. Loci across a minimal 50-Mb region of primarily the long arm of chromosome 17 showed LOH in 8 cases, whereas a less than 9-Mb region of loci flanking NF1 had LOH in the remaining 2 cases. Two complementary techniques, quantitative polymerase chain reaction (PCR) and fluorescence in situ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 47 publications
5
45
0
Order By: Relevance
“…44 Recently, it has been described that affected children with NF1 may develop myeloid malignancies after losing their wild-type NF1 allele due to interstitial uniparental disomy. 45 To date, mutations in NF1 have not been identified in adult patients with any myeloid disorders 46 but, it has been recently demonstrated that hemizygotic NF1 mice are more sensitized to carcinogenic stimuli, which result in hematological disorders independent of mutation of Trp53. 47 The NF1 gene has also been shown to be downregulated by the AML1-ETO fusion gene, which represses NF1 gene expression, resulting in RAS overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…44 Recently, it has been described that affected children with NF1 may develop myeloid malignancies after losing their wild-type NF1 allele due to interstitial uniparental disomy. 45 To date, mutations in NF1 have not been identified in adult patients with any myeloid disorders 46 but, it has been recently demonstrated that hemizygotic NF1 mice are more sensitized to carcinogenic stimuli, which result in hematological disorders independent of mutation of Trp53. 47 The NF1 gene has also been shown to be downregulated by the AML1-ETO fusion gene, which represses NF1 gene expression, resulting in RAS overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…28 Several constitutional (not tumor-associated) segmental UPD regions have been detected in infant ALL patients, but not in normal newborns (aged o1 year), with the UPD(14)(q21.2) as the most recurrent. As UPD has been proposed to be a selective mechanism involved in leukemogenesis, [18][19][20] we investigated whether it could be responsible for the duplication of oncogenic mutations. Sequencing of the whole coding region of the FANCM gene in patients with UPD(14)(q21.2), although confirming the homozygous status of all the SNPs contained in the sequence, did not reveal any mutations.…”
Section: Discussionmentioning
confidence: 99%
“…17 UPD is an emerging finding in both ALL and acute myelogenous leukemia patients, for whom it has been associated with homozygous gene mutations sustaining disease progression and chemoresistance. 16,[18][19][20] Nevertheless, extended runs of homozygosity (ROH) have been found in normal individuals, [21][22][23] resulting from different degrees of inbreeding. ROHs among unrelated patients lead to the identification of new genes or candidate loci responsible for the genetic basis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer, this arises as a duplication of a region containing a mutation that frequently, but not always, behaves as a tumor suppressor gene, as has recently been shown to occur in cases of NF1-associated JMML. 21,22 To determine if additional regions of uniparental isodisomy exist in JMML, we performed single-nucleotide polymorphism array analysis (Genome-Wide Human SNP Array 6.0, Affymetrix, Santa Clara, CA) on samples from 27 JMML patients with and without known PTPN11, RAS, or NF1 abnormalities. 3 We identified a region of 11q uniparental disomy in five of these cases.…”
Section: Pediatric Malignanciesmentioning
confidence: 99%